Do We Need a Gwent Tier 3 FCAMHS Neurodevelopmental Assessment Pathway? - Andrew Todd; Michael Jones; Adam Edwards; Nicola Crawley; Danielle John (BJPsych Open)
Aims: There are high rates of Neurodevelopmental Disorders (NDD) and mental health needs in young people who engage in offending behaviours. Incompletely assessed development can be a factor in engaging with legal proceedings and with those involved in their care. Young people open to the three Gwent Youth Offending Services (YOS) and Tier 3 Gwent Forensic Child & Adolescent Mental Health Service (FCAMHS) have previously been identified as having traits indicative of an underlying NDD. No specific ND assessment pathways exist within YOS for suspected Autism Spectrum Disorder (ASD) and/or Attention Deficit Hyperactivity Disorder (ADHD); those requiring assessment are referred to the CAMHS ND Team. Some cases are Not in Education, Employment or further Training (NEET), may not reside with family, and can struggle to engage in typical referral pathways.